2014
DOI: 10.1016/j.anorl.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Medical treatment of osteoradionecrosis of the mandible by PENTOCLO: Preliminary results

Abstract: The PENTOCLO protocol achieved clinical and radiological regression of ORN with, in parallel, a reduction of the indications for major surgery. These preliminary results need to be confirmed by prospective studies comprising quality of life assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 20 publications
0
72
0
7
Order By: Relevance
“…Early results have been encouraging. [7][8][9] It can be difficult to avoid the onset of ORN in patients who have had radiotherapy for cancer of the head and neck, as the risk increases throughout life. Obvious triggers include dental extractions, but more subtle events, including denture trauma, dental infection, and the insertion of dental implants, have also been implicated.…”
Section: Introductionmentioning
confidence: 99%
“…Early results have been encouraging. [7][8][9] It can be difficult to avoid the onset of ORN in patients who have had radiotherapy for cancer of the head and neck, as the risk increases throughout life. Obvious triggers include dental extractions, but more subtle events, including denture trauma, dental infection, and the insertion of dental implants, have also been implicated.…”
Section: Introductionmentioning
confidence: 99%
“…Clodronate is an oral bisphosphonate used for the treatment of deficiencies in calcium absorption or certain malignancies. Robard et al [30] observed a clinical and radiographic improvement in ORN using the PENTO protocol with clodronate and reported that it reduced pain and improved both food intake and mouth opening. Meanwhile, Rice et al [31], in evaluating ORN treatment options, conclude that for advanced or refractory cases, surgical treatments are the only option.…”
Section: Discussionmentioning
confidence: 97%
“…5,14,16 Em relação aos cuidados locais, nenhum dos artigos selecionados especificou como esses cuidados foram realizados. Na literatura essa abordagem é diversa, com utilização de digluconato de clorexidina e iodopovidona para limpeza das feridas.…”
Section: Discussionunclassified
“…Os efeitos inibitórios sobre os osteoclastos é 1000 vezes inferior aos outros bisfosfonatos e a concentração utilizada no tratamento da ORN é menor que em outras indicações. 5 As publicações E1 e E4 avaliaram a eficácia do PENTOCLO: associação da pentoxifilina (PTX), tocoferol e clodronato e o E6 não incluiu clodronato por relutância devido à experiência com osteonecrose associada ao bifosfonato. No entanto, as…”
unclassified